Study of biological properties of Leptospira interrogans serovar Canicola strains as candidate components of human leptospirosis concentrated inactivated vaccine - A. A. Trotsenko; M. V. Kovrizhko; E. A. Yagovkin; V. S. Vanzha; А. A. Reshetov (Биопрепараты: Профилактика, диагностика, лечение, 2021)
Leptospirosis is a widespread zoonosis in Russia. The human leptospirosis vaccine produced by Rostov Research Institute of Microbiology and Parasitology has been used since 1998 to minimise risks associated with deterioration of epidemiological situation. Lately, there has been an increase in the incidence of leptospirosis caused by Leptospira interrogans serovar Canicola which is not included in the human vaccine. The aim of the study was to analyse biological properties of Leptospira interrogans serovar Canicola strains to substantiate their inclusion into human leptospirosis liquid concentrated inactivated vaccine. Materials and methods: two L. interrogans serovar Canicola strains: Udalov 480 and Sobaka 2000 were used in the study. Virulent properties of the strains were evaluated by infecting Syrian hamsters, the data on specific activity of the experimental vaccine were compared to specific activity of the leptospirosis liquid concentrated inactivated vaccine used for disease prevention. The experimental vaccine was tested for Specific safety and Abnormal toxicity according to FS.3.3.1.0014.15 Leptospirosis liquid concentrated inactivated vaccine. Results: the comparison of Udalov 480 and Sobaka 2000 strains of L. interrogans serovar Canicola revealed higher virulence of Udalov 480. The tests performed for the experimental vaccine batches demonstrated that the inclusion of Udalov 480 strain did not affect the above-mentioned properties of the vaccine. Conclusions: the study demonstrated the possibility of using L. interrogans serovar Canicola strain Udalov 480 as a component of the currently produced vaccine, and confirmed the safety and efficacy of the new vaccine.